Atmospheric rivers in the Arctic: Physical processes and impact on the surface energy budget - Tiedeck, Sofie (Dr.) (2025)
The Arctic climate system has changed rapidly in recent decades, with mean warming exceeding 2 K, making it the global warming hotspot. This phenomenon, known as Arctic Amplification, is driven by feedback mechanisms reacting to anthropogenic greenhouse effects, including cloud radiative effects, water vapor feedback and temperature feedbacks. Poleward moisture transport also shows changes correlating with Arctic warming. A substantial part of this transport occurs via so-called “Atmospheric Rivers” (ARs). These narrow atmospheric bands are often linked to extratropical cyclones, and transport moist and warm air into polar regions. ARs are linked to sea ice melt, precipitation in both the form of rain and snow, suggesting a warming effect on the Arctic surface. This thesis examines the influence of ARs on the Arctic surface energy budget (SEB) through case studies in early winter and spring, combining ERA5 reanalysis data (1979-2021) and regional simulations with the ICON model. Sensitivity studies explore how lateral moisture inflow affects the SEB, analyzed from Eulerian and Lagrangian perspectives for detailed process insights. Using the Guan-Waliser AR detection algorithm and ERA5, the climatological impacts of ARs on the surface fluxes, as well as moisture, cloud content, and skin temperatures are statistically quantified, with trends assessed between the "old Arctic" (1979-1999) and "new Arctic" (2000-2021). Two AR types are distinguished: moisture-dominated (“wet”) and wind-dominated (“windy”). Furthermore, the occurrence of ARs in the Atlantic Sector is linked to atmospheric circulation regimes. ARs generally warm the Arctic surface, with a strong dependence on the season and surface type. Winter ARs over open ocean show the strongest impact. Overall, the SEB anomalies are mostly dominated by turbulent flux anomalies (latent and sensible heat), i.e. near-surface temperatures and moisture. Radiative effects from increased liquid water and vapor lead to stronger terrestrial downward radiation. In summer, ...